Organizational change, psychosocial work environment, and non-disability early retirement: a prospective study among senior public employees - Nina Breinegaard; Johan Høy Jensen; Jens Peter Bonde (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVE: This study examines the impact of organizational change and psychosocial work environment on non-disability early retirement among senior public service employees. METHODS: In January and February 2011, Danish senior public service employees aged 58-64 years (N=3254) from the Capital Region of Denmark responded to a survey assessing psychosocial work environment (ie, social capital, organizational justice, and quality of management). Work-unit organizational changes (ie, change of management, merging, demerging, and relocation) were recorded from January 2009 to March 2011. Weekly data on non-disability early retirement transfer were obtained from the DREAM register database, which holds weekly information about all public benefit payments in Denmark. Hazard ratios (HR) for early retirement following employees' 60^th birthday were estimated with Cox regression adjusted for age, gender, and socioeconomic status. RESULTS: Exposure to change of management [HR 1.37, 95% confidence interval (95% CI) 1.13-1.66], mergers (HR 1.23, 95% CI 1.02-1.48), and relocation of work unit (HR 1.24, 95% CI 1.01-1.54) increased rate of non-disability early retirement, while demerging of work unit did not (HR 1.03, 95% CI 0.79-1.33). Work units with lower levels of social capital (HR 1.22, 95% CI 1.05-1.41), organizational justice, (HR 1.18, 95% CI 1.04-1.32), and quality of management (HR 1.14, 95% CI 1.02-1.25) increased rate of early retirement. CONCLUSION: Organizational change and poor psychosocial work environment contribute to non-disability early retirement among senior public service employees, measured at work-unit level.